Epidemiological characteristics of three herpesviruses infections in children in Nanjing, China, from 2018 to 2023 - Wei, Mingwei; Zhang, Yang; Li, Zhibin; Liang, Qi (Frontiers in Cellular and Infection Microbiology, 2024)
ObjectiveTo evaluate the epidemiology characteristics of Herpes simplex virus type 2 (HSV-2), Epstein-Barr virus (EBV) and Cytomegalovirus (CMV) infection in children from January 2018 to December 2023, in Nanjing, China.MethodsWe conducted a retrospective analysis of 21,210, 49,494 and 32,457 outpatients and inpatients aged 1 day to 17 years who were subjected to the three herpesviruses (HSV-2, EBV, and CMV) nucleic acid testing from January 2018 to December 2023, respectively. Demographic information, laboratory findings, etc. were collected and analyzed. HSV-2, EBV and CMV nucleic acid testing were performed by real-time PCR.ResultsThe total rate of detection of the three herpesviruses for all specimens was 0.32% (67/21,210), 14.99% (7419/49,494), and 8.88% (2881/32,457), respectively. A declining trend in the incidence of viral infections over the years was observed for the three herpesviruses (all P<0.05). The detection rate for HSV-2, EBV, and CMV was highest among patients aged 1-3 years, 3-7 years, and 28 days to 1 year, respectively (all P<0.05). The presence of HSV-2 and CMV infection did not exhibit a discernible seasonal pattern, whereas EBV typically demonstrated an elevation during the summer and autumn.ConclusionEBV and CMV were both prevalent among children in China, except for HSV-2. The annual prevalence of the three herpesviruses show decreasing trend from 2018 to 2023, and no difference in gender (except for EBV). EBV infections usually occur in the summer and autumn, whereas HSV-2 and CMV do not exhibit significant seasonality. The positivity rate of HSV-2 is highest in 1-3 years, EBV is highest in 3-7 years, and that of CMV is highest in 28 days to 1 year. Positive detection rates are higher in outpatients than in inpatients.